Work-family conflict and its relationship with turnover intentions: the moderating role of agreeableness and neuroticism - Chang, Dionise Sze Yun (Nanyang Technological University, 2024)
This cross-sectional survey study examines the moderating influence of agreeableness and neuroticism on the relationship between work-family conflict (WFC) and turnover intentions among nurses from four public hospitals in Singapore (N = 106). Results reveal a significant main effect of WFC on turnover intentions, indicating that higher levels of WFC correspond to increased turnover intentions. However, neither agreeableness nor neuroticism demonstrated a significant moderating effect. Nevertheless, the study contributes to the practical understanding and expands on the limited literature on personality traits, WFC, and turnover intentions within nursing. Moreover, the findings underscore the detrimental impact of turnover on nurses, patients, and hospital outcomes, while offering strategies to mitigate turnover. Several limitations and avenues for future research were discussed.